Radiographic Prevalence of Osteochondrosis in Yearling Feral Horses - Valentino, L. W.; Lillich, J. D.; Gaughan, E. M.; Biller, D. R.; Raub, R. H. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
The purpose of the study is to document the prevalence of articular surface osteochondrosis lesions in feral horses. Eighty yearling feral horses were used. Radiographic images of the left stifle, both tarsocrural, metatarsophalangeal, metacarpophalangeal joints were taken. Radiographs were examined for the presence of osteochondral fragmentation and abnormal outline of subchondral bone suggestive of osteochondrosis. The prevalence of each lesion was calculated for each joint as well as for overall prevalence within the group, the latter being 6.25%. Typical osteochondrosis lesions were found within the tarsocrural and metatarsophalangeal joints. Based on the difference in prevalence of osteochondrosis between feral and certain domestic horses, management practices and perhaps genetic base may have a greater influence on the development of the disease in horses than trauma alone.
Keywords: Osteochondrosis; radiographic survey; feral horses